Weaving colourful threads: A tapestry of spirituality and mysticism - Kourie, Celia (HTS teologiese studies, 2015)
Given the plethora of research conducted in the field of spirituality and mysticism over the last 30 years, it is almost a superhuman feat to keep up with the explosion of information. Of necessity, in a limited article of this nature, it is possible to discuss only a few salient aspects of the spirituality and mysticism phenomenon and by so doing contribute to ongoing research in this important domain. Contemporary spiritualties encompass the whole range of human experience and new variants are emerging; for example, the relatively recent Contemplative Studies, a cognate and close companion to Spirituality. Crossing inter-religious boundaries enhances studies in Mysticism; natural mysticism is clearly in the foreground; and breaking research in neurotheology sheds light on the nature of the ‘mystical mind’. Discussion of the value or otherwise of techniques and methods of the mystical journey continues unabated. Of great value for today’s frenetic, Internet-crazy world is the path of mystical silence. By contributing to a discussion of these issues, it is hoped that the threads of spirituality and mysticism will continue to share their colour in a world desperate for beauty and peace.